STATE OF ENTREPRENEURSHIP EDUCATION IN MALAYSIA: A COMPARISON OF ENTREPRENEURSHIP PROGRAMS IN PUBLIC UNIVERSITIES IN MALAYSIA TO INTERNATIONAL PRACTICE - Sabirah, Sulaiman; Siti Nur Liyana, Mohd Yusof; Mazdan, Ali Amaran (UUM PRESS, 2024)
This study provides a comprehensive exploration of entrepreneurship education in Malaysia, focusing on institutional and government initiatives to stimulate innovation, economic growth, and job creation. Despite compulsory entrepreneurship subjects in public universities, a significant rise in graduate entrepreneurs remains elusive. The study assesses the state of entrepreneurship programs in Malaysian institutions and benchmarks them against Babson College in the United States.Content analysis and interviews with 12 successful entrepreneurs scrutinize program outcomes and course offerings at Universiti Utara Malaysia and Universiti Malaysia Kelantan, comparing them with Babson College. Secondary data, obtained through desktop reviews, illuminate Malaysia’s entrepreneurship education courses, assessed through university websites. Literature searches across databases and primary qualitative data offer in-depth insights, employing a mixed-methods approach to comprehensively address the research problem.Triangulation enhances data credibility, while qualitative and quantitative data from experienced entrepreneurs provide practical implications. Findings underscore the need for foundational entrepreneurship education, practical skills, and diverse courses. They emphasize a shift from a grade-centered to an experiential learning-focused approach, echoing calls for educational reform